The Effects of Different Heat Preservation Methods on the Antioxidant Activity of Ambarella (Spondias Dulcis) Fruit Juice - Hanis Nadia Y; I. N. Mohd Nasir; L Karim; Hafiza Yahya (SASPR Edu International Pvt. Ltd, 2026)
Ambarella (Spondias dulcis) is a tropical plant with excellent phytochemicals properties and has long been used in many traditional medical practices. This study aimed to evaluate the effects of different heat preservation methods; pasteurization (85ºC in 30 seconds), water bath canning (100ºC in 10 minutes) and jar processing (121ºC in 1 minute), on the antioxidant activity of Ambarella (Spondias dulcis) fruit juice. The Total Phenolic Content (TPC) of Ambarella juice was determined using Folin-Ciocalteu’s assay, while DPPH (1,1-diphenyl-2-picrylhydrazy) was used to analyze the free radical scavenging activity. The reducing power of Ambarella juice was assessed using Ferric Reducing Antioxidant Power (FRAP). The result of Folin-Ciocalteu’s assay showed that the highest TPC value was detected in the raw juice (5.3002 ± 0.114 mg GAE/g) while the lowest was in the water bath juice (3.6137 ± 0.174 mg GAE/g). The result of free radical scavenging activity of the juice samples found that pasteurized juice exhibited the highest percentage of scavenging activity (55.81 ± 0.55%), while retorted juice was the lowest (33.44 ± 0.61%). The highest reducing power was obtained in the raw juice (98.30 ± 0.85%), while water bath juice recorded the lowest percentage of reducing power (65.66 ± 0.68%) out of all juice samples tested. The correlation between the total phenolic contents and antioxidant activities was determined as a positive, linear correlation with DPPH (r = 0.407) and FRAP (r 0.963). Similarly, a positive correlation was also observed between both of the DPPH and FRAP antioxidant assays (r = 0.625). The pasteurization method was determined as the best heat preservation method compared to water bath canning and jar processing, since it exhibited comparatively high TPC value and higher antioxidant activity percentage.